A língua em Graça: enunciação em Infância, de Graciliano Ramos. - Andrade Neto, Austriclínio Bezerra de (2023)
We propose, through this study, to contribute to the established debate on the approximation of Émile Benveniste's enunciative thought with literature. A complex debate, considering the peculiarity of the French linguist's writing and the scarcity of the author's organic products on the subject. However, such relationship finds theoretical and pragmatic support, evidenced by the resources to literary works in several texts and in the attempts of theoretical formulations in their manuscripts. We delve into the Benvenistian subjective moment to promote this approximation, having as an empirical object the autobiography Infância by the Alagoan writer Graciliano Ramos. We also refer to the works by Arfuch (2010), Calame (1986), Dosse (2015), Flores (2013, 2019a, 2019b); Greimas (1974), Hamburger (2013), Henry (2013) and Lejeune (2011) to think about an enunciative subjectivity and its presence in autobiography, a text that figures within the limits of language, in terms of the tenuous border between ordinary language and the literary. A text characterized by the imbrication between writer, narrator and character, in terms of the discursive genre it represents. The reflections point to the importance of carrying out studies of this nature, which respond to the invitation by Benveniste himself, that many stimuli should be thought of in the context of the enunciation. A promising field for thinking about language, continuing inconclusive studies and expanding the scope of Émile Benveniste's theory of enunciation.